Without using calculator

Algebra Level 3

What is the value of t a n ( π 7 ) . t a n ( 2 π 7 ) + t a n ( 2 π 7 ) . t a n ( 4 π 7 ) + t a n ( 4 π 7 ) . t a n ( π 7 ) tan(\frac{\pi}{7}).tan(\frac{2\pi}{7}) + tan(\frac{2\pi}{7}).tan(\frac{4\pi}{7}) + tan(\frac{4\pi}{7}).tan(\frac{\pi}{7}) ?


The answer is -7.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Bitan Sarkar
Jul 6, 2017

We will start from, c o s ( A + B ) = c o s A . c o s B s i n A . s i n B t a n A . t a n B = 1 c o s ( A + B ) c o s A . c o s B cos(A + B) = cosA.cosB - sinA.sinB \Rightarrow tanA.tanB = 1 - \frac{cos(A +B)}{cosA.cosB} Using this property,

t a n ( π 7 ) t a n ( 2 π 7 ) + t a n ( 2 π 7 ) t a n ( 4 π 7 ) + t a n ( 4 π 7 ) t a n ( π 7 ) tan(\frac{\pi}{7}) tan(\frac{2\pi}{7})+tan(\frac{2\pi}{7})tan(\frac{4\pi}{7}) +tan(\frac{4\pi}{7}) tan(\frac{\pi}{7})

= 3 ( c o s 3 π 7 c o s π 7 . c o s 2 π 7 + c o s ( 6 π 7 ) c o s 2 π 7 . c o s 4 π 7 + c o s ( 5 π 7 ) c o s 4 π 7 . c o s π 7 ) = 3 - (\frac{cos\frac{3\pi}{7}}{cos\frac{\pi}{7}.cos\frac{2\pi}{7}} + \frac{cos(\frac{6\pi}{7})}{cos\frac{2\pi}{7}.cos\frac{4\pi}{7}} + \frac{cos(\frac{5\pi}{7})}{cos\frac{4\pi}{7}.cos\frac{\pi}{7}})

= 3 c o s ( 4 π 7 ) c o s ( π 4 π 7 ) + c o s ( 2 π 7 ) c o s ( π 2 π 7 ) + c o s ( π 7 ) c o s ( π π 7 ) c o s π 7 . c o s 2 π 7 . c o s 4 π 7 = 3 - \frac{cos(4\frac{\pi}{7})cos(\pi - 4\frac{\pi}{7}) + cos(2\frac{\pi}{7})cos(\pi - 2\frac{\pi}{7}) + cos(\frac{\pi}{7})cos(\pi - \frac{\pi}{7})}{cos\frac{\pi}{7}.cos\frac{2\pi}{7}.cos\frac{4\pi}{7}}

= 3 + c o s 2 ( 4 π 7 ) + c o s 2 ( 2 π 7 ) + c o s 2 ( π 7 ) c o s π 7 . c o s 2 π 7 . c o s 4 π 7 = 3 + \frac{cos^2(4\frac{\pi}{7}) + cos^2(2\frac{\pi}{7}) + cos^2(\frac{\pi}{7})}{cos\frac{\pi}{7}.cos\frac{2\pi}{7}.cos\frac{4\pi}{7}}

Now, c o s π 7 . c o s 2 π 7 c o s 4 π 7 = 1 8 cos\frac{\pi}{7}.cos\frac{2\pi}{7}cos\frac{4\pi}{7} = -\frac{1}{8} Proof given below.

= 3 8 ( c o s 2 ( 4 π 7 ) + c o s 2 ( 2 π 7 ) + c o s 2 ( π 7 ) ) = 3 - 8(cos^2(4\frac{\pi}{7}) + cos^2(2\frac{\pi}{7}) + cos^2(\frac{\pi}{7})) 2 c o s 2 A = 1 + c o s 2 A \because 2cos^2A = 1 + cos2A

= 3 4 ( 3 + c o s ( 2 π 7 ) + c o s ( 4 π 7 ) + c o s ( 8 π 7 ) ) = 3 - 4(3 + cos(\frac{2\pi}{7}) + cos(\frac{4\pi}{7}) + cos(\frac{8\pi}{7}))

= 3 4 ( 3 + c o s ( 2 π 7 ) + c o s ( 4 π 7 ) + c o s ( 6 π 7 ) ) = 3 - 4(3 + cos(\frac{2\pi}{7}) + cos(\frac{4\pi}{7}) + cos(\frac{6\pi}{7}))

Now, c o s ( 2 π 7 ) + c o s ( 4 π 7 ) + c o s ( 6 π 7 ) = 1 2 cos(\frac{2\pi}{7}) + cos(\frac{4\pi}{7}) + cos(\frac{6\pi}{7}) = -\frac{1}{2} Proof given below.

So, t a n ( π 7 ) t a n ( 2 π 7 ) + t a n ( 2 π 7 ) t a n ( 4 π 7 ) + t a n ( 4 π 7 ) t a n ( π 7 ) tan(\frac{\pi}{7}) tan(\frac{2\pi}{7})+tan(\frac{2\pi}{7})tan(\frac{4\pi}{7}) +tan(\frac{4\pi}{7}) tan(\frac{\pi}{7})

= 3 4 × ( 3 1 2 ) = 3 - 4 \times (3 - \frac{1}{2})

= 7 = -7

Proof 1 : c o s π 7 . c o s 2 π 7 c o s 4 π 7 cos\frac{\pi}{7}.cos\frac{2\pi}{7}cos\frac{4\pi}{7}

Proof 2 :

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...